Multi-System Langerhans Cell Histiocytosis as a Mimic of IgG4-Related Disease: A Case Report and Literature Review - Feng, Xiaohui; Zhang, Lu; Chen, Fuqiong; Yuan, Gang (Frontiers in Endocrinology, 2022)
Langerhans cell histiocytosis (LCH) is a rare disease characterized by the clonal accumulation and/or proliferation of specific dendritic cells resembling normal epidermal Langerhans cells (LCs). Clinical manifestations are variable, depending on the affecting tissues or organs, however, LCH with elevated serum IgG4 has not been reported. Herein, we reported a 26-year-old Chinese female multi-system LCH (MS-LCH) who firstly represented with central diabetes insipidus (CDI), accompanied by panhypopituitarism and hepatic dysfunction. Diagnostic investigations were strongly suspicious of IgG4-RD because of elevated serum IgG4 level during the process. Furtherly, thyroid and lymph node involvement and biopsy led to the diagnosis of MS-LCH; the strongly positive staining of CD1a, S100, CD207 (langerin), Ki67 was found. Moreover, after systemic treatment with chemotherapy for 5 times, many lesions greatly improved. Since both LCH and IgG4-RD are orphan diseases which can affect any organs, the differential diagnosis is challenging, especially when LCH is associated with unexplained serum IgG4 elevation. In this article, the case of a young woman suffering from MS-LCH that affected organs including pituitary, thyroid, lymph node and liver was summarized and relevant literature was reviewed in order to provide help for better equipping to diagnose and treat it in its early stages.